Konseling Individu Dengan Teknik Refarming Dalam Membangun Resiliensi Pada Remaja (Studi Kasus Pada Klien “A” Di Kelurahan Mariana) - Nova Ramadhana; Zhila Jannati; Bela Janare Putra (Journal of Innovative and Creativity, 2025)
This study, entitled "Individual Counseling with the Reframing Technique in Building Resilience in Adolescents (A Case Study on Client 'A' in Mariana Village)", aims to examine (1) the resilience of client “A” before individual counseling with the reframing technique, (2) the implementation of individual counseling with the reframing technique in building resilience in client “A”, and (3) the resilience of client “A” after individual counseling with the reframingtechnique. This research uses a qualitative approach with a case study method, collecting data through observation, interviews, and documentation, and analyzing it using pattern matching, data explanation, and time-series analysis. The results show that (1) before counseling, client “A” had low resilience characterized by unstable emotions, negative thinking, and a lack of family support; (2) individual counseling with the reframing technique effectively helped build resilience by transforming negative perceptions into positive and constructive ones; and (3) after counseling, client “A” showed increased resilience, better emotional regulation, clear life goals, and improved relationships with family members. These findings indicate that individual counseling with the reframing technique can be an effective approach to help individuals build resilience and improve their quality of life.